Tagalog language patterns of greeting, farewell, address, compliment, and obeisance - Cruzate, Lourdes O. 1935- (s.n.], 1970)
The purpose of the study is to describe the language patterns of greeting, farewell, address, compliment, and odeisance in Tagalog and their relation to variables like sex, status, age, and social situation. The study aims to provide a baseline for further research in relation to language teaching. Results of the study will serve as a guide in the determination of teaching techniques and procedures, in the selection of subject matter, and in the preparation of instructional materials.